2021
DOI: 10.1002/celc.202100366
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Anodic and Cathodic Dissolution of Gold by Varying the Surface Roughness

Abstract: This work presents the reactivity and dissolution of an aspolished and electrochemically pre-treated polycrystalline Au electrode, which is used as a model system. The effect of the electrochemical pre-treatment in corrosive 0.37 M HCl solutions on the Au surface roughness and dissolution is investigated by varying the number of pre-treatment steps at 1.16 V against the reversible hydrogen electrode. It is shown that the first 10 s pretreatment of the as-polished Au results in a higher surface roughness and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 37 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Corrosion of the Au leaf is assisted by its thinness ( 32 ), roughness ( 16 ), and Ag content ( 5 , 33 ). Corrosion is further enhanced by the Cl − -rich environment ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Corrosion of the Au leaf is assisted by its thinness ( 32 ), roughness ( 16 ), and Ag content ( 5 , 33 ). Corrosion is further enhanced by the Cl − -rich environment ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In closing, the electrochemical oxidation/dissolution of Au is a complex subject usually studied under laboratory conditions using ad hoc equipment, methods, and thermodynamic approaches ( 16 , 39 ). Conversely, here, we propose a pioneering robust model that sheds light on the degradation of bimetallic artistic gilding, including Au dissolution and AuNP precipitation under natural conditions in a Cl − -rich medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,8,57,58] Indeed, it has been shown that polycrystalline Au can undergo potential-dependent anodic dissolution via a variety of mechanisms under acidic conditions, especially for electrodes having a high roughness factor. [23,57,58,87] There is evidence from both theory and experiment that this dissolution is more pronounced for AuNPs smaller than 1.5 nm. [4,7,8,24,60,61,88] The foregoing literature studies of Au dissolution at positive potentials are directly relevant to our interpretation of the results in the present study.…”
Section: Proposed Mechanism Of Np Growth During Cleaning Scansmentioning
confidence: 99%
“…[7,8,13,16,[20][21][22] Even for polycrystalline gold surfaces, the rate of anodic Au dissolution during potential cycling is highly dependent on the surface structure of the electrode. [23] These atomic-level structural changes are further exacerbated for very small (<~5 nm) NPs due to their inherent instability. [24][25][26][27] The foregoing problems are further compounded by the fact that in some cases electrocatalytic NPs are only characterized immediately after synthesis, less frequently after catalysis, and generally not at all during or after cleaning protocols.…”
Section: Introductionmentioning
confidence: 99%